Painless nondiabetic lumbosacral radiculoplexus neuropathy with complete recovery: a case report - Zhibin Tan; Wai Dic Foong; You-Jiang Tan (Journal of Medical Case Reports, 2023)
Abstract Background Lumbosacral radiculoplexus neuropathy, also known as amyotrophy, is an uncommon monophasic disorder characterized by inflammation of the lumbosacral nerve roots and plexuses. Lumbosacral radiculoplexus neuropathy is usually associated with diabetes mellitus, is typically painful at presentation, and often associated with long-term residual neurologic deficits. We report a case of painless, nondiabetic lumbosacral radiculoplexus neuropathy in a young Chinese woman, who made a full recovery after treatment with intravenous immunoglobulin, adding an atypical case to the scarce literature on lumbosacral radiculoplexus neuropathy. Case presentation A 35-year-old Chinese woman presented to our emergency department with 1-week history of painless left lower limb weakness and numbness. Examination revealed weakness confined to the left lower limb but spanning various nerves and myotomes, with abnormal sensation. Clinical localization to the lumbosacral plexus was supported by neurodiagnostic tests, and magnetic resonance imaging of the lumbosacral plexus showed that the nerve roots were also involved. After treatment with intravenous immunoglobulin for nondiabetic lumbosacral radiculoplexus neuropathy, the patient had a full recovery. Conclusion Our patient’s case highlights that lumbosacral radiculoplexus neuropathy, an already rare disorder, can occur in the absence of diabetes mellitus and pain, making it even harder to recognize. A systematic and meticulous clinical approach, supported by intelligent selection of adjunctive tests, is required for localization and diagnosis. With an accurate diagnosis, our case also demonstrates that appropriate and prompt treatment can lead to complete recovery, despite previous reports suggesting a high prevalence of long-term residual deficits after lumbosacral radiculoplexus neuropathy.